2013
DOI: 10.1371/journal.pntd.0002453
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Microbiota of Gingival Lesions in Noma Patients

Abstract: Noma (cancrum oris) is a gangrenous disease of unknown etiology affecting the maxillo-facial region of young children in extremely limited resource countries. In an attempt to better understand the microbiological events occurring during this disease, we used phylogenetic and low-density microarrays targeting the 16S rRNA gene to characterize the gingival flora of acute noma and acute necrotizing gingivitis (ANG) lesions, and compared them to healthy control subjects of the same geographical and social backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…More precisely, acute noma seems to be characterized by the diminution of Capnocytophaga and Fusobacteria genera and by the increase of Prevotella genus. 15,36,37 Indeed, Prevotella intermedia was already reported in previous studies undertaken with classical cultures. 35 Prevotella intermedia is a well-known periodontal pathogen in adults, but it has been detected also in the primary dentition of small children.…”
Section: Noma Sequelaementioning
confidence: 72%
“…More precisely, acute noma seems to be characterized by the diminution of Capnocytophaga and Fusobacteria genera and by the increase of Prevotella genus. 15,36,37 Indeed, Prevotella intermedia was already reported in previous studies undertaken with classical cultures. 35 Prevotella intermedia is a well-known periodontal pathogen in adults, but it has been detected also in the primary dentition of small children.…”
Section: Noma Sequelaementioning
confidence: 72%
“…Less specific, in terms of infected tissues is Noma, a gangrenous disease that affects maxillary of children with compromised immune function. This is most probably a polymicrobial infection, however, it has been demonstrated that S. pyogenes and S. anginosus (among other non-streptococcal species) are more abundant in the gingival microbiota of Noma patients with acute necrotizing gingivitis compared to healthy controls ( Huyghe et al, 2013 ).…”
Section: Diseases Caused By Oral Streptococcimentioning
confidence: 99%
“…A recent study conducted by Hughye et al 18 contradicted the involvement of Fusobacterium necrophorum as an etiologic agent. Known periodontal pathogens like aggregatibacter actinomycetemcomitans, capnocytophaga, porphyromonia and fusobacteria were more prevalent in healthy samples compared to those with noma.…”
mentioning
confidence: 94%